Age-related increase in the expression of 11β-hydroxysteroid dehydrogenase type 1 in the hippocampus of male rhesus macaques - Lomniczi, Alejandro; Luna, Selva L.; Cervera-Juanes, Rita; Appleman, Maria-Luisa; Kohama, Steven G.; Urbanski, Henryk F. (Frontiers in Aging Neuroscience, 2024)
Introduction The hippocampus is especially susceptible to age-associated neuronal pathologies, and there is concern that the age-associated rise in cortisol secretion from the adrenal gland may contribute to their etiology. Furthermore, because 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1) catalyzes the reduction of cortisone to the active hormone cortisol, it is plausible that an increase in the expression of this enzyme enhances the deleterious impact of cortisol in the hippocampus and contributes to the neuronal pathologies that underlie cognitive decline in the elderly. Methods Rhesus macaques were used as a translational animal model of human aging, to examine age-related changes in gene and protein expressions of (HSD11B1/HSD11B1) in the hippocampus, a region of the brain that plays a crucial role in learning and memory. Results Older animals showed significantly (p < 0.01) higher base-line cortisol levels in the circulation. In addition, they showed significantly (p < 0.05) higher hippocampal expression of HSD11B1 but not NR3C1 and NR3C2 (i.e., two receptor-encoding genes through which cortisol exerts its physiological actions). A similar age-related significant (p < 0.05) increase in the expression of the HSD11B1 was revealed at the protein level by western blot analysis. Discussion The data suggest that an age-related increase in the expression of hippocampal HSD11B1 is likely to raise cortisol concentrations in this cognitive brain area, and thereby contribute to the etiology of neuropathologies that ultimately lead to neuronal loss and dementia. Targeting this enzyme pharmacologically may help to reduce the negative impact of elevated cortisol concentrations within glucocorticoid-sensitive brain areas and thereby afford neuronal protection.